Evaluation of the physical and physical chemical characteristics of araçá Psidium brownianum Mart. ex DC. (Araçá-de-veado) (Research, Society and Development, 2020)
The araçazeiro is a fruit tree native to Brazil, belonging to the Myrtaceae family, and can be found from the state of Rio Grande do Sul, through Minas Gerais, to the Northeast region. There are many species of araçá, but depending on the region there are different interests in carrying out studies about its characterization, pointing out that this fruit has excellent physical-chemical characteristics, great economic potential and can be considered indispensable in the regeneration of degraded areas.  These fruit characteristics make the araçazeiro a new and promising option for cultivation, bringing benefits to consumers and becoming an alternative for sustainable exploitation for small rural producers. The processing of native fruits as araçá meets the growing industrial interest for exotic products, besides being extremely accepted by consumers. As for the araçá fruits existing in the Araripe Forest, no information on physical and chemical parameters was found in the literature, thus the objective was to determine the physical and chemical characteristics (SS, pH, AT, SS/AT, reducing and non-reducing sugars) and physical characteristics such as: whole fruit mass, pulp mass, pulp yield. From the results obtained for araçá it was possible to verify that due to its low degree of sweetness it does not have great acceptance for consumption of the fruit in natura. It presents potential for industrialization and one of the contributing factors is the uniformity of format, slightly rounded, good yield in pulp, low pH and high concentrations of acidity.